The relationship between accounting practices and business performance: literature review study of SMEs in the service industry - Rina Apriliani; Teguh Prakoso (Junal Ilmu Manajemen, 2023)
This literature review examines the relationship between accounting practices and business performance in small and medium-sized enterprises (SMEs) in the service industry. The study follows a systematic review methodology, including a comprehensive search of academic databases using relevant keywords and a thorough screening process to identify studies that meet the inclusion criteria. The data analysis involves a thematic analysis of the selected studies, focusing on the types of accounting practices used by SMEs, the performance indicators used to measure business performance, and the strength of the relationship between accounting practices and business performance. The implications for practice suggest that SMEs in the service industry can benefit from implementing financial accounting practices to improve their business performance. However, the use of management accounting practices should be evaluated carefully. Suggestions for further research include investigating the moderating factors that affect the relationship between accounting practices and business performance, such as the external environment and the availability of resources.